PERANCANGAN APLIKASI BERBASIS ANDROID UNTUK KOMUNITAS PENGGEMAR BURUNG KICAU - Dian Sano, Albert V; Muhammad, Bintang Fadhli; Mangare, Edward Kristian; Jason, Jeremy; Hidayah, Taufiq (ISTEK WIDURI, 2019)
Industry 4.0 is developing and industry 4.0 is the name of the latest automation and data exchange trends in manufacturing technology. This term covers physical-cyber systems, the internet for everything, cloud computing, and cognitive computing. Industry 4.0 produces